(untitled) (Research, Society and Development, 2020)
This study aims to report the experience developed in a 9th grade class at a state school, from the use of the advertising propaganda genre. From this study, it was possible to develop communicative awareness in deaf students, in addition to favoring the expansion of LIBRAS vocabulary. In this sense, we use the advertising metaphor in Portuguese language classes with the prospect of developing the deaf learner’s awareness and communicative competence for deaf young people who finish 9th grade of elementary school. The proposal was developed in the Portuguese language subject as L2 for the Deaf, with 06h duration (referring to two classes lasting three hours each), having as target audience deaf students of the 9th grade of primary school. As the objective for this activity we chose: to understand the process of understanding metaphors in advertising for the development of awareness and communicative competence of deaf learners in the Portuguese language classes as L2 in the writing modality. As a result, we point out the advance of students in communication in LIBRAS, as well as the expansion of vocabulary, in addition to enabling interaction with other students.